Shoulder range of motion in elite tennis players. Effect of age and years of tournament play - Kibler, W. B.; Chandler, T. J.; Livingston, B. P.; Roetert, E. P. (The American Journal of Sports Medicine, 1996)
We studied glenohumeral rotational range of motion in 39 members of the United States Tennis Association National Tennis Team and touring professional program. We took goniometric measurements of internal and external rotation of dominant and nondominant shoulders at the glenohumeral joint with the humerus at 90 degrees of abduction. We categorized the tennis players by age and by years of tournament play. Results were analyzed by total rotation, internal rotation, external rotation, and dominant-to-nondominant shoulder differences. In our results, dominant internal rotation of the shoulder declined and the difference between dominant and nondominant internal rotation increased with both age and years of tournament play. Men and women tennis players showed the same degree of deficits in range of motion. Significant analysis of variance statistics were calculated for dominant internal rotation with years of total play, dominant total rotation with years of total play, and nondominant total rotation with age. Moderate negative correlations were found between dominant internal rotation and years of total play and dominant total rotation and years of total play. These results indicate a loss of internal rotation that seems progressive with longer periods of play. This loss of internal rotation of the shoulder is an absolute loss of motion because total rotation also decreases. Early detection and a corrective training program should be considered because adaptations may result in deleterious biomechanics affecting both performance and risk of injury.